MNEMONIK MASHQLAR VOSITASIDA INGLIZ TILIDAN OʻQUVCHILARNING NUTQIY KOʻNIKMALARINI SHAKLLANTIRISHNING ILMIY-NAZARIY ASOSLARI - Karlibayeva, A.Ye. (SCIENCE and SOCIETY, 2025)
The article provides information about mnemonic exercises aimed at developing the lexical competence of students of higher educational institutions in English, and their meaning.
Keywords: mnemonics; speech skills; communication; lexical units; semantic analysis; linguistic data